Multi-Perspective Decision-making Cloud Computing Adoption Model for Small and Medium Enterprises (SMEs) - Can Sayginer; Tuncay Ercan (Emerging Science Journal, 2020)
The research aims to test the model of integrated DOI theory and TOE framework to predict Cloud Computing (CC) decision-making intentions of SMEs, Izmir, Turkey. The survey data was collected from 140 Information Technology (IT) decision-makers via Google forms survey tool. Confirmatory factor analyses were made to examine the decision-making approach of SMEs. The study revealed that the variance of top management support and complexity explained 29.8% of the decision-making approach to CC adoption. The originality of the study is that the research on cloud computing in Turkey is scarce and not comprehensive either. In addition, they are not for Turkish SMEs. This research will bring together an introductory plan for cloud providers to understand the intentions of SMEs for adopting cloud computing. This research will also provide scholars with an in-depth analysis of the status contributing to the academic research in the field of ICT development in developing countries. This study will contribute to SMEs’ ICT infrastructure policies, and support governments in creating a legal framework to make laws for a secure environment for SMEs to reduce costs, and gain a competitive advantage over Large Enterprises (LEs). Doi: 10.28991/esj-2021-SP1-010 Full Text: PDF